THỬ NGHIỆM, ĐÁNH GIÁ BỘ KIT AMPLISENS® HPV HCR GENOTYPE-FRT CHẨN ĐOÁN VÀ ĐỊNH TYPE HUMAN PAPILLOMA VIRUS - Bùi, Thị Tuyết; Trần, Văn Trưởng; Nguyễn, Văn Hiệp; Nguyễn, Văn Khanh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATION OF A AMPLISENS® HPV HCR GENOTYPE-FRT FOR HUMAN PAPILLOMAVIRUS DETECTION AND GENOTYPING CAUSING CERVICAL CANCERPersistent infection with oncogenic human papillomavirus (HPV) genotypes has been shown to be necessary for the development of cervical cancer. The recently developed AMPLISENS® HPV HCR GENOTYPE-FRT assay (HPV Amp-genotype assay) is based on simultaneous PCR (multiplex - PCR) and Real-time to detect 12 HPV types (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59) and β-globin gene, used as internal control, in 4 tubes. Each HPV type is registered on its channel, that allows not only to detect the presence of HPV DNA, but also to differentitate the virus genotype. The aim of this study was to evaluate the performance of the HPV Amp-genotype assay for detecting HPV genotypes and comparing the results with those obtained in combination of the AmpliSens® HPV HCR screen-titre-FRT PCR 4x (HPV Amp-screen assay), LightPower HPV Genotype PCR-HPV GENOTYPE RDB (HPV GENOTYPE RDB assay) and Kit LightPower iVAHPV PCR Plus assay (PCR plus assay). We found high similarity between HPV Amp-genotype assay and others (88,09% - 86,6%- 89,55%; Cohen’s kappa coefficients = 0,745- 0,698-0,734). The limit of detection of HPV Amp-genotype assay was 1,14.103 copies/ml, it wasmore sensitive than other assays. In conclusion, the HPV Amp-genotype assay is an alternative test for HPV genotyping in clinical laboratories.